Becoming Fugitive: Migration in the American and EurAfrican Borderlands - Gross-Wyrtzen, Leslie; Vázquez López, Alondra (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2023)
This article tells the stories of illegalized migrant people moving through two violent, transcontinental borderscapes: the EurAfrican border that spans Western Europe, the Mediterranean Sea, and pushes further south each year across Africa; and the American border that stretches from the interior of the United States, through Mexico and Central America, and into South America and the Caribbean. Comparative analysis of these borderscapes reveals similar logics, practices, and policies of border enforcement, as well as strategies that migrant people use to subvert them. We argue that fugitivity provides a critical lens for understanding the co-constitution of borders and border transgression, and reveals how the border manufactures its objects—producing fugitive subjects, spaces, and relations across expanding spatial and temporal distances. As a lens rooted in histories of racialized control over human mobility, fugitivity allows us to chart contemporary territorializations of racial domination through bordering alongside constant challenges to these territorializations through movement. Ultimately, fugitivity provides a method that not only maps out the violence and failures of bordering, but one that imagines alternative geographies emanating from the underground of marginalized people, spaces, and relationships.